Визначення референтних величин мінеральної щільності структур стегнової кістки для рентгенівської остеоденситометрії - Уданович, Д. Г.; Арсенідзе, Т. О. (ХНУРЭ, 2017)
The report describes a methodology that allows to objectivize the definition of mineral density of the bone tissue by x-ray images, obtained by photodensitometry, which is based on measurements of the optical density of bone radiographs. The dose of irradiation is the same as with conventional X-ray that X-rays are performed on the diagnosis of any other pathology, including dysplasia of the hip joint, and the results are expressed as an equivalent of the thickness of the test object.Changing the shape of the densitogram of the x-ray bone image is primarily due to changes in the density or thickness of the bone tissue layer, which may obviously occur with many pathological disorders
Keywords: биомединженерия; кісткова тканина